De escola prim?ria a Centro Universit?rio de Cultura e Arte (CUCA): a hist?ria de um patrim?nio edificado em Feira de Santana-BA no s?culo XX - Santana, Leonardo Justino (2024)
This dissertation investigates how the University Center for Culture and Art (CUCA) in Feira de Santana, Bahia, has become a cultural heritage. The study focuses on the way in which CUCA offers culture to the community and seeks to integrate local culture into its agenda, highlighting its role in preserving and promoting the region's cultural identity. The research starts from the observation of a gap in discussions about historical heritage in undergraduate and postgraduate courses in History at the State University of Feira de Santana (UEFS), proposing a qualitative analysis that uses bibliographic and documentary sources and the built heritage itself. from CUCA. The work explores the various concepts of heritage in force at the institution, transcending its physical dimension to understand its impact on the city of Feira deSantana. The study highlights the importance of expanding academic research on historical and cultural heritage, demonstrating how CUCA serves as a significant example of living heritage, which not only preserves, but also energizes local culture by integrating it into its activities. Furthermore, the dissertation seeks to contribute to a deeper understanding of the role of Heritage Education in the preservation and enhancement of cultural heritage, with a special focus on CUCA as a vital center for the culture and identity of Feira de Santana.